Program Penguatan Perilaku Abstinensi Berbasis Operant Conditioning pada Klien Rehabilitasi Adiksi di Klinik IPWL BNN RI - Sabrina Rizkyana; Alisha Sarah Atia; Nanda Rahma Kartikasari; Aftina Nurul Husna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Substance abuse is a health and social problem that can reduce an individual's physical, psychological, social relationships, and quality of life, as well as increase the risk of relapse. This community service activity aims to implement an Operant Conditioning-Based Abstinence Behavior Strengthening Program for outpatient rehabilitation clients at the IPWL BNN RI Clinic. The program is implemented through six sessions of positive behaviorism-based individual counseling that include reinforcement, trigger identification, adaptive coping formation, extinction of maladaptive beliefs related to substance use, and preparation of a coping plan. Evaluation is carried out through observation, interviews, intervention worksheets, and measurements using the SRQ, URICA, and WHOQoL-BREF. The results show an increase in the URICA score from 18 to 23 and an increase in quality of life in the physical (16-22), psychological (16-23), social relationships (18-22), and environmental (15-19) domains. Clients also demonstrated more adaptive coping skills and a more realistic perception of substance use. This program has the potential to support rehabilitation and relapse prevention in substance abuse clients.